BUSINESS PLANNING FOR SMART KIDS DAYCARE IN CIMAHI CITY - Reja Apriangga Nugraha; Yenny Maya Dora (Politeknik Negeri Ambon, 2026)
Daycare Smart Kids is an early childhood daycare business located in South Cimahi, offering an integrated service concept that combines professional childcare, thematic educational stimulation, and regular psychological and medical monitoring. This business responds to the needs of young families, especially working parents seeking a safe, comfortable, and developmentally supportive childcare solution. Based on market analysis and demographic data, South Cimahi shows strong potential, marked by the growing number of young families and increased female workforce participation. The limited availability of daycare centers that meet high educational and safety standards gives Daycare Smart Kids a strategic position in the market. Its services include flexible membership options, daily, weekly, and monthly real-time CCTV access for parents, and a curriculum focused on character and creativity development. The primary target market includes middle-income young families in Cimahi and West Bandung, with an expected annual customer growth rate of over 12%. Financially, this project is highly viable. With a total initial investment of Rp 236,273,750, the payback period is projected at 2 years and 3 months. The business demonstrates strong performance indicators, including a Net Present Value (NPV) of Rp 460,503,349, an Internal Rate of Return (IRR) of 48%, and a Profitability Index (PI) of 2.95. Return on Investment (ROI) stands at 302%, while the Gross Profit Margin (GPM) and Net Profit Margin (NPM) are 60.81% and 15.25%, respectively, indicating high operational efficiency and profitability. The business is projected to generate positive cash flow starting in the third year, signaling a timely transition from investment phase to profitability. The competitive advantages of Daycare Smart Kids lie in its certified human resources, modern and child-friendly learning facilities, the use of digital technology, and operations aligned with the national TARA standard. The business plan is developed through Design Thinking, the Business Model Canvas, SWOT analysis, and the Timmons model, ensuring readiness across entrepreneurship, market, and resource aspects. With a solid planning foundation and a promising market landscape, Daycare Smart Kids is well-positioned to become a trusted, sustainable, and leading daycare solution in South Cimahi. Keywords: Business Planning, Marketing Strategy, Business Model Canvas